Hubungan Body Image dan Kepercayaan Diri dengan Perilaku Konsumtif Penggunaan Produk Kosmetik: Implikasinya terhadap Bimbingan dan Konseling - Khariidah Syafaa’ Putri Yanuar; Ulfa Rosada (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study aims to examine the partial and simultaneous relationships between body image, self-confidence, and consumptive behavior regarding cosmetic products among adolescent female students. Methods – A quantitative correlational design was employed. The research respondents comprised 222 female students in grades X and XI selected through a sampling technique. Data were collected using three scaled instruments: a body image scale, a self-confidence scale, and a consumptive behavior scale. Data analysis was performed using multiple linear regression and path analysis via statistical software. Findings – Path analysis results indicated that when controlled together, body image had a very weak positive and statistically non-significant direct relationship with consumptive behavior (?= 0.065, p = 0.351). Conversely, self-confidence exhibited a strong, negative, and highly significant relationship with consumptive behavior (? = -0.505, p < 0.001), identifying it as the core predictor. Simultaneously, both variables were significantly related to consumptive behavior (F = 31.780, p < 0.001), accounting for 22.5% of the total variance.Research Implications – This study underscores that adolescent consumptive behavior toward cosmetics is primarily driven by psychological factors like self-confidence rather than body perception. Guidance and counseling practitioners should prioritize interventions aimed at enhancing self-confidence and rational decision-making to mitigate impulsive purchasing. Methodologically, this study is limited to a single school sample and relies on self-reported questionnaires, suggesting that future research should incorporate broader geographical locations and potential mediating variables.